The right to the judicial participation of children and adolescents in the Judicial System of Peru: advances and challenges - Seminario Hurtado, Nuccia (2019)
This article aims to analyze the progress and challenges of the right to judicial participation of children and adolescents in the Peruvian judicial system. Likewise, the development of the general and specific foundation attributed to this right from the perspective of the framework for the protection of the human rights of children and adolescents